FAKTOR-FAKTOR PENDORONG KEBERHASILAN PENANAMAN NILAI KEJUJURAN DAN KETAATAN PADA SISWA DI SDI - Fatahuddin; Hidayat, Dafid Fajar; M. ALI MUHSON (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
Children as a mandate for parents who are born in a state of purity. What they will be made into when they grow up, depends on the pattern of education given in childhood. Especially in childhood is the strongest structural basis for building the physical and spiritual structure of children. Therefore, in order to avoid development errors, especially the spiritual structure of children, parents must instill the values of honesty and obedience to children. SDI NU . Cingkirejo Maduretno Papar Kediri as one of the educational institutions that tries to solve these problems with an educational pattern that prioritizes the cultivation of the values of honesty and obedience. The focus of research in this thesis includes 1) The practice of instilling the value of honesty, 2) Obedience to teachers 3) related to the strategy of PAI teachers in instilling the value of honesty and obedience in their students. The conclusion of the results of this study is 1) Instilling honesty values in students at SDI NU Cingkirejo Maduretno.Papar Kediri by providing good examples, encouraging parents so that their children follow pesantren kilat during school holidays, ordering and involving in religious activities, sending children to madrassas and telling children to participate in reciting at TPA. 2) Instilling the values of obedience in students at SDI NU Cingkirejo Maduretno Papar Kediri includes: teachers bear a great responsibility because children are entrustments / trusts from Allah SWT. and to break the generation. 3) PAI teachers' strategies in instilling vocational values and obedience to students at SDI NU Cingkirejo Maduretno Papar Kediri include: faith values, worship values, promise values, threats, and punishments, as well as moral values. Anak sebagai amanat bagi orang tua. Akan dijadikan apa saat mereka dewasa, tergantung pola pendidikan yang diberikan pada masa kecil. Masa anak-anak adalah dasar struktur terkuat untuk membangun jasmani dan rohani anak. Agar tidak terjadi kesalahan, dalam rohani anak, orang tua harus menanamkan nilai-nilai kejujuran dan ketaatan kepada anak SDI sebagai salah satu lembaga pendidikan yang berusaha memecahkan masalah tersebut dengan pola pendidikan yang mengutamakan penanaman nilai-nilai kejujuran dan ketaatan. Faktor-faktor pendorong keberhasilan penanaman nilai-nilai kejujuran dan ketaatan pada siswa SDI adalah dengan memberikan ilmu dan contoh teladan yang baik, mengajurkan orang tua agar anaknya mengikuti pesantren kilat pada saat libur sekolah, memperintahkan dan melibatkan dalam kegiatan keagamaan, menyekolahkan anak di madrasah dan menyuruh anak ikut mengaji di TPA sekaligus guru juga memikul tanggung jawab besar karena anak adalah titipan atau amanah dari Allah. Strategi guru PAI dalam pananaman nilai-nilai kejuruan dan ketaatan pada siswa di SDI meliputi: nilai keimanan, nilai ibadah, nilai janji, ancaman, dan hukuman, serta nilai akhlak. Penelitian ini masih memiliki keterbatasan area penelitian, sehingga hasilnya tidak dapat digeneralisikan. Penulis juga menyadari masih banyak kekurangan dan untuk penelitian selanjutnya disarankan bisa meneliti secara lebih spesifik setiap komponen dan mampu memberikan sumbangan signifikan kepada strategi pendidikan agama islam